2019
DOI: 10.1002/bio.3651
|View full text |Cite
|
Sign up to set email alerts
|

Silicon nanoparticles synthesized using a microwave method and used as a label‐free fluorescent probe for detection of VB12

Abstract: A simple and rapid detection strategy for vitamin B 12 (VB 12 ) was established based on label-free silicon quantum dots (SiQDs); the detection mechanism was additionally investigated. SiQDs were synthesized using a one-step microwave method, and their fluorescence was stronger than that synthesized using the hydrothermal method.SiQDs fluorescence was quenched using VB 12 due to the inner filter effect (IFE), which was demonstrated using ultraviolet (UV) absorption spectra, fluorescence lifetime, transmission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Long et al realized silicon QDs with a size of 4-5 nm which they employed to detect VitB12, the presence of which was demonstrated to quench the fluorescence of silicon QDs due to the inner filter effect. Fluorescence quenching efficiency was observed to monotonically increase as a function of the VitB12 concentration, thus allowing the detection of VitB12 with an LoD of 158 nmol L −1 [96]. Pourreza et al demonstrated a fluorescence method based on the use of chitosan-embedded Ag nanoparticles which interact with VitB12, cloud point extraction, and the subsequent detection using fluorescence.…”
Section: How To Monitor the Deficiency Of Vitb12: Involvement Of Nanomentioning
confidence: 99%
“…Long et al realized silicon QDs with a size of 4-5 nm which they employed to detect VitB12, the presence of which was demonstrated to quench the fluorescence of silicon QDs due to the inner filter effect. Fluorescence quenching efficiency was observed to monotonically increase as a function of the VitB12 concentration, thus allowing the detection of VitB12 with an LoD of 158 nmol L −1 [96]. Pourreza et al demonstrated a fluorescence method based on the use of chitosan-embedded Ag nanoparticles which interact with VitB12, cloud point extraction, and the subsequent detection using fluorescence.…”
Section: How To Monitor the Deficiency Of Vitb12: Involvement Of Nanomentioning
confidence: 99%
“…They are mainly obtained by the reaction of a silicon source and reducing agent. Methods of synthesizing water-soluble SiNPs included the water bath method, , room temperature stirring method, , microwave-assisted method, , post-modification method, , and one-pot hydrothermal method. , In recent years, the one-pot hydrothermal method has been widely applied to the synthesis of water-soluble SiNPs owing to its superiority of simple operation, inexpensive equipment, and excellent optical properties of the synthesized materials. Compared with traditional fluorescent quantum dots, water-soluble SiNPs are simple in composition and free of heavy metal elements.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the simple synthesis and excellent properties, SiNPs were considered as ideal fluorescent probes in the fields of analytical science. Lately, fluorescent probes based on SiNPs were successfully used to detect heavy metal ions, , dopamine, amino acids, vitamins, nitro explosives, etc. Furthermore, SiNPs could also be used for pH sensing and bioimaging. , Nevertheless, the application of SiNPs in the detection of active ingredient of Chinese medicine is relatively rare.…”
Section: Introductionmentioning
confidence: 99%